2019
DOI: 10.1159/000502174
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor-Producing Bladder Cancer

Abstract: Granulocyte colony-stimulating factor (G-CSF)-producing bladder cancer is rare, with only 75 cases reported in Japan. A 67-year-old woman was referred to our institution for the further examination of gross hematuria. Cystoscopy revealed a 7-cm bladder tumor. The initial white blood cell count was 17,100/μL, and a transurethral resected specimen showed G-CSF expression. CT revealed that the tumor had invaded the colon. As the patient had uncontrollable schizophrenia, radical cystectomy was abandoned. We herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Several studies have documented cross talk between cancer and immune cells, but also inflammatory factors that are expressed by the TME, such as the CSF family of cytokines, which attract macrophages (through CCL2 and VEGFA) [ 29 , 30 , 31 , 32 ]. We have shown that G-CSF is highly expressed in GI cancers [ 17 , 33 ] and is associated with tumor progression and poor prognosis in several other cancer types, such as prostate [ 34 ], neuroblastoma [ 35 ], bladder [ 36 ], non-small cell lung cancer [ 37 ], and head and neck squamous cell carcinomas [ 38 ]. However, little is known regarding the role of the G-CSF in the TME, particularly related to immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented cross talk between cancer and immune cells, but also inflammatory factors that are expressed by the TME, such as the CSF family of cytokines, which attract macrophages (through CCL2 and VEGFA) [ 29 , 30 , 31 , 32 ]. We have shown that G-CSF is highly expressed in GI cancers [ 17 , 33 ] and is associated with tumor progression and poor prognosis in several other cancer types, such as prostate [ 34 ], neuroblastoma [ 35 ], bladder [ 36 ], non-small cell lung cancer [ 37 ], and head and neck squamous cell carcinomas [ 38 ]. However, little is known regarding the role of the G-CSF in the TME, particularly related to immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes align with the observations made by Bajorin et al during the pre-immunotherapy era, when cisplatin-based therapy was primarily the established treatment protocol [ 33 ]. Leukocytosis, as indicated in previous reports, may be linked to tumors that produce granulocyte colony-stimulating factor (G-CSF), and this association is correlated with a less favorable prognosis [ 34 ]. Similarly, anemia has been identified as an independent factor associated with reduced OS and CSS among urothelial carcinoma patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] This condition is rare, although only several case reports have shown leukocytosis in a patient with bladder cancer due to a G-CSF-producing tumor. [ 13 14 15 ] G-CSF has also been associated to tumor cell proliferation which is aggressive and has a poor clinical outcome. [ 15 ] This condition can explain the cause of poor prognosis and short survival in this study.…”
Section: Discussionmentioning
confidence: 99%